Analisis Efektivitas Modal Kerja Terhadap Rentabilitas Perusahaan (Studi Kasus Pada Perusahaan Koperasi KPRI Kanca Winaya, Kecamatan Klari Kabupaten Karawang - Acim Supriadi (Program Studi Akuntansi, 2018)
This study aims to determine the financial performance of the aspect of working capital effectiveness on corporate rentability on KPRI KancaWinaya Cooperative. The method used in this research, is survey method (explanatory) with descriptive approach (condition variable) and verifikatif (influence variable). That is the research that tries to tell the existing problem solving based on the data, present the data, analyze and interpret it. To achieve the objectives of the study, an analysis of the working capital (net working capital), working capital report has been calculated along with current ratio calculation and net working capital ratio to measure short-term financial health, and evaluate the result of source analysis and capital use work in that period. Then, to know how big the contribution of working capital (qualitative concept), or net working capital as independent variable to rentability of company calculated by using formula of calculation of simple correlation coefficient. The results showed that the development / addition of working capital KPRI Kanca Winaya company in the period of 2012 to 2016, continues to increase. Similarly, the development of profitability of the company from 2012 to 2016 has increased and pluktuatif decline. Current ratio and net working capital ratio shows that the management of fund flows (source and use of funds) is not effective or not in accordance with the basic concept of fund flow management. While the results of correlation coefficient calculation shows the value of correlation coefficient T of 0.47. Where the value of correlation coefficient T = 0.47 is in position> 0 (greater than zero); meaning there has been a positive linear relationship. That is the greater the value of variable X (independent / working capital), then the greater the value of variable Y (dependent / economic rentability). Or the smaller the value of variable X, the smaller the value of variable Y.